Large-signal modeling method for power FETs and diodes - 孙璐 王家礼 王珊 李雪铮 石慧 王娜 郭生平 (Journal of semiconductors, 2009)
Under a large signal drive level,a frequency domain black box model of the nonlinear scattering function is introduced into power FETs and diodes.A time domain measurement system and a calibration method based on a digital oscilloscope are designed to extract the nonlinear scattering function of semiconductor devices.The extracted models can reflect the real electrical performance of semiconductor devices and propose a new large-signal model to the design of microwave semiconductor circuits.